Идеальная афера - Леонов Николай Иванович (Русский бестселлер, 2015)
Экземпляры: аб. ЦБ (2016.13.12) / Инвентарный номер: 2673 / Цена: 135.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л 47 / ББК: 84(2Рос=Рус)6